An Anonymous Off‐Line Credit Card System Based on ITLs. Issue 5 (May 2014) - Ohashi, Yusuke; Tamura, Shinsuke; Taniguchi, Shuji
SUMMARY This paper proposes a scheme for anonymous off‐line credit card systems that enables cardholders to make purchases from shops anonymously while being disconnected from card companies, that is, without using information maintained by card companies or other shops. The proposed scheme is an extension of the ITL (Implicit Transaction Link) based one for online anonymous credit card systems that had been proposed already. As same as the original online scheme, the proposed extended scheme does not assume any absolutely trustworthy neutral entity or tamper‐resistant device.